Impact of COVID-19 on fish and crustacean export from China with building resilient food system through China's lens - Nisar, Ubair; Zhang, Zhixin; Cui, Zhaocai; Mu, Yongtong; Zhang, Hongzhi (Frontiers in Sustainable Food Systems, 2023)
For China's fish and crustacean trade globally, the COVID-19 pandemic outbreak in 2020 has posed previously unprecedented challenges. This study investigates these concerns by analyzing China's fish and crustacean export activities and correlating the shift in trade throughout the pre-pandemic and pandemic phases. Despite the numerous factors for the changing trade, this research attempts to explain those related to the pandemic and coping mechanisms. The investigation is supported by and linked to a conceptual framework for the resilience of the perishable agricultural food system by China during the pandemic. The results indicated that fish and crustacean exports from China decreased as the incidence of infections increased both globally and within the country. Trade with important markets including Japan, Korea, and the United States was badly affected by the outbreak. While shipments to Korea saw the fastest growth throughout the pandemic, the monthly growth rate of fish exports to the USA was the lowest. However, China's fish and crustacean trade recovered well after the epidemic, with faster growth rates and lower instability. The pandemic even resulted in a decrease in the unit value realized for all fish and crustacean commodities. The government's long-term efforts to ensure food security and prompt policy responses during the outbreak have demonstrated that China's food system can endure and rebound from perturbations. China's "green route" for perishable agricultural goods in the domestic market and prohibition on illegal obstructions serve as examples of how to maintain supply flow during an outbreak.